2013
DOI: 10.4236/abb.2013.42a037
|View full text |Cite
|
Sign up to set email alerts
|

Pectin shows antibacterial activity against <i>Helicobacter pylori</i>

Abstract: Pectins are the collective name for a group of heterogeneous, high molecular weight, branched polysaccharides that are found in the cell walls of higher plants. In this study, we intend to determine the antibacterial activity of pectin against reference strains and clinical isolates of Helicobacter pylori. The results show that pectin produced antibacterial effects on all the 16 clinical isolates and 2 reference strains of H. pylori with the greatest antibacterial effect at a low pH (5.0) versus higher pHs. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…Previous studies that involved evaluating functionalities of different oligosaccharides showed the tremendous potential of oligosaccharides in various aspects related to health and disease. Functional oligosaccharides have been found effective in gastrointestinal normal flora proliferation and pathogen suppression, dental caries prevention, enhancement of immunity, facilitation of mineral absorption, source of antioxidant, antibiotic alternative, regulators of blood glucose in diabetics, and serum lipids in hyperlipidemics [7]. Xylooligosaccharides in pharmaceutical preparations exhibit antiallergy, antimicrobial, anti-infection, and anti-inflammatory properties, selective cytotoxicity, and immunomodulatory action [10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies that involved evaluating functionalities of different oligosaccharides showed the tremendous potential of oligosaccharides in various aspects related to health and disease. Functional oligosaccharides have been found effective in gastrointestinal normal flora proliferation and pathogen suppression, dental caries prevention, enhancement of immunity, facilitation of mineral absorption, source of antioxidant, antibiotic alternative, regulators of blood glucose in diabetics, and serum lipids in hyperlipidemics [7]. Xylooligosaccharides in pharmaceutical preparations exhibit antiallergy, antimicrobial, anti-infection, and anti-inflammatory properties, selective cytotoxicity, and immunomodulatory action [10].…”
Section: Discussionmentioning
confidence: 99%
“…Pectins are found to have antimicrobial potential against the methicillin resistant Staphylococcus aureus and Aspergillus niger [6]. Pectin also showed antibacterial activity against Helicobacter pylori [7].…”
Section: Introductionmentioning
confidence: 99%
“…In 2013, scholars in Lebanon reported the significant antibacterial activity of citrus pectin against all 16 clinical isolates and 2 reference strains of Gram-negative Helicobacter pylori, a common human pathogen and public health problem that causes gastritis and peptic ulcers. [20] Once again, the highest antibacterial activity was observed at pH 5.0 and lower activity at higher pH values, with a minimum inhibitory concentration (MIC) of 0.162 mg/mL and minimum bactericidal concentration (MBC) of 0.325 mg/mL. Two years later, the same team reported that optimal antibacterial activity against S. aureus and E. coli was observed at pH 6, with MIC values against S. aureus ranging between 0.39 mg/mL and 3.125 mg/mL and minimum bactericidal concentration (MBC) varying in the ample range 3.125-12.5 mg/ mL.…”
Section: A Broad-spectrum Antimicrobialmentioning
confidence: 99%
“…Not only is pectin a broad-spectrum antimicrobial agent whose in vitro [1,5,6,7,12,19,20] and in vivo [14,15,16] activity has long been established in thorough laboratory and clinical trials, but low methoxyl pectin is also a biomaterial whose exceptional biocompatible nature and superior rheological properties make it ideally suited as an injectable cell vehicle for bone tissue regeneration. [26] In the latter case, a low degree of esterification is required because the galacturonic acid groups are functionalized with an RGD-containing oligopeptide (RGD, Arg-Gly-Asp).…”
Section: A Broad-spectrum Antimicrobialmentioning
confidence: 99%
“…Polysaccharides from natural sources, including fucoidans, may have a direct bactericidal influence on various microorganisms. Thus, the bactericidal action of citrus pectin, which is a branched, high molecular weight polysaccharide found in the cell walls of higher plants, against H. pylori has been described in the literature . The bactericidal effect of pectin was established for 16 clinical and two reference strains of the causative agent.…”
Section: The Direct Bactericidal Effect Of Sulfated Polysaccharidesmentioning
confidence: 99%